2019
DOI: 10.1016/j.nepr.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ perceptions towards being taught the fundamentals of care by clinical nurses within a simulated learning environment: A qualitative study

Abstract: Research in nursing education demonstrates that the fundamentals of care are paid less attention in this field resulting in negative consequences for students' learning outcomes. The aim of this qualitative study was to explore nursing students' perceptions towards being taught the fundamentals of care by clinical nurses within a simulated learning environment. The study has a qualitative explorative design. Data was collected through participant observation and focus group interviews and analysed using qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…The empirical data were generated through observations of and focus group interviews with the clinical nurses and students. These findings are presented in the earlier papers for this project (Lillekroken, 2019a, ). Given the lack of empirical studies that focus on nurse educators' perceptions about teaching fundamental care within a simulated learning environment, an additional focus group interview with nurse educators was conducted in November 2018.…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…The empirical data were generated through observations of and focus group interviews with the clinical nurses and students. These findings are presented in the earlier papers for this project (Lillekroken, 2019a, ). Given the lack of empirical studies that focus on nurse educators' perceptions about teaching fundamental care within a simulated learning environment, an additional focus group interview with nurse educators was conducted in November 2018.…”
Section: Methodssupporting
confidence: 71%
“…Moreover, the results from a pilot study conducted by Alderman et al () offered a practical and feasible way to explicitly embed the fundamentals of care into nursing curricula. Recently, a qualitative study conducted by Lillekroken (, ) focused on clinical nurses' teaching and students' learning the fundamentals of care within a simulated learning environment, revealing how the fundamentals of care are taught and learned. The findings demonstrated that nurses from clinical settings are capable and competently teaching fundamental care in a simulated learning environment.…”
Section: Introductionmentioning
confidence: 99%
“…This process provides an opportunity for active participation of students, and it is focused on error prevention, immediate feedback, and creation of an appropriate training environment, where students will feel and actually be psychologically safe, will communicate among them, and be able to review the process. Participation in small groups allows the students to directly monitor the attempts made by their classmates, improve their methods and enhance solidarity among them ( 36 , 37 ). Simulation establishes a bridge between theory and clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…Answering students' questions thoroughly and accurately, being confident, promoting student independence, looking organized, and encouraging active involvement during discussion were the five most essential elements, listed by the students. Indeed, practical knowledge is constructed through social dialogue between students, clinical nurses and nursing faculty (Lillekroken, 2019). Students have opportunities to ask questions in order to get new knowledge and advance their level of learning, while teachers can offer responses at the same moment, ensuring by this way continuous feedback (Havery, 2019;Lillekroken, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This requires multiple avenues for clinical learning, mainly how to maintain relationships and interactions with patients and the team members in a way that keeps feedback ongoing (Hsu, 2014) and helps develop a very positive relationship with the clinical teacher. In order to maintain motivation among nursing students, ensure their satisfaction with the clinical learning experience and judge their performance effectively (Chan et al, 2017;Lillekroken, 2019;Salamonson et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%